The TRIMendous Role of TRIMs in Virus–Host Interactions - Sarah van Tol; Adam Hage; Maria Isabel Giraldo; Preeti Bharaj; Ricardo Rajsbaum (Vaccines, 2017)
The innate antiviral response is integral in protecting the host against virus infection. Many proteins regulate these signaling pathways including ubiquitin enzymes. The ubiquitin-activating (E1), -conjugating (E2), and -ligating (E3) enzymes work together to link ubiquitin, a small protein, onto other ubiquitin molecules or target proteins to mediate various effector functions. The tripartite motif (TRIM) protein family is a group of E3 ligases implicated in the regulation of a variety of cellular functions including cell cycle progression, autophagy, and innate immunity. Many antiviral signaling pathways, including type-I interferon and NF-κB, are TRIM-regulated, thus influencing the course of infection. Additionally, several TRIMs directly restrict viral replication either through proteasome-mediated degradation of viral proteins or by interfering with different steps of the viral replication cycle. In addition, new studies suggest that TRIMs can exert their effector functions via the synthesis of unconventional polyubiquitin chains, including unanchored (non-covalently attached) polyubiquitin chains. TRIM-conferred viral inhibition has selected for viruses that encode direct and indirect TRIM antagonists. Furthermore, new evidence suggests that the same antagonists encoded by viruses may hijack TRIM proteins to directly promote virus replication. Here, we describe numerous virus–TRIM interactions and novel roles of TRIMs during virus infections.